Psychological Practice in the Bodies of Internal Affairs: Current Condition and Perspectives - Ulyanina O.A (Moscow State University of Psychology and Education, 2017)
The article describes the main directions and reveals the content of psychological work in the bodies of internal affairs which is continuously implemented at each stage of staff performance. Among the leading areas of activity of psychologists are the following: professional psychological selection of candidates for service; psychological diagnosis of employees in the course of support of official activity; the study of the socio-psychological climate in the collectives and the moral and psychological state of the personnel; carrying out special psychophysiological studies using a polygraph; adaptation of young employees; professional psychological training of personnel; psychological prevention and correction of negative psychoemotional states; psychological counseling of personal, family and professional problems of employees. Taking into account the described state of the departmental psychological service, the prospective directions of its development are outlined, and the need to implement a systemic, integrated approach when solving problems related to the psychological maintenance of staff performance is emphasized.